The shared benefit approach to competitiveness - Esparza Rodríguez, Saúl Alfonso; Martínez Arroyo, Jaime Apolinar (Mercados y Negocios, 2019)
The purpose of this article is to show a new approach to measure competitiveness in organizations by introducing a measurement of processes capabilities index concerning meeting needs and expectation of essential stakeholders. The argument initiates of considering a logical syllogism that relates identifying and fulfilling stakeholders needs and expectations with organization competitiveness, second compare two-way investments and benefits received among stakeholders and organizations and then proposes the use of process capability index to measure the competitiveness regarding stakeholder’s management. An example of any given company is used to explain a quantitative approach and the use of a calculated cpk index to measure organizations capabilities regarding shared interest. The proposition shows a proposed general model of equilibrium in the shared benefit that can explain a quantitative approach of the capacity of the organization to manage stakeholders.